Court-mandated interventions for individuals convicted of domestic violence: an updated Campbell systematic review - Wilson, David B. (Campbell Systematic Reviews, 2021)
This is an update of our prior review. The aim was to assess the effects of postarrest court-mandated interventions for intimate partner violence offenders that target, in part or exclusively, male batterers. Our focus was on studies aimed at reducing intimate partner violence, above and beyond what would have been expected by routine legal procedures (e.g., probation monitoring, etc.).